Reaching the one billion mark: accomplishing the success story of COVID vaccination through public interrogation - Sarkar, Avir; Roy, Kallol Kumar; Zangmo, Rinchen; Jayraj, Aarthi K.; Kaushik, Durga; Rai, Rakhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The COVID vaccination drive in India has recently crossed the one billion mark which is certainly a tremendous feat. Although women were initially hesitant, public propaganda and behaviour change communications encouraged them to come forward. The aim of the study was to assess the vaccination status of female population of the country through interrogation in obstetrics and gynaecology out patient departments (OBG OPD). Methods: Through this cross-sectional study, all women visiting OBG OPD were asked about type and number of vaccine doses received, dates of administration of first and second doses and whether they had any significant side effects following immunization. Results: A total of 1456 women were recruited in the study. Mean age of participants was 33.24±4.65 years. 36.26% participants were pregnant. 89.97% women had received at least one dose of vaccine and 48.76% participants were fully vaccinated. Majority received Covishield vaccine. Majority of the participants received first shot during the months of July, August and September. No women suffered from any adverse effect following immunization. Most women got motivated for vaccination from television (76.91%) and alert messages in mobile phones (61.59%). The results of our study reflects the success story of vaccination campaign as almost 90% of the participants had received at least one dose of vaccine. Conclusions: The proactive participation and untiring efforts of the frontline workers has been instrumental in achieving this remarkable landmark. India’s successful vaccination campaign is a lesson to the world at large.